An Examination of Distributed and Decentralized Systems for Trustworthy Control of Supply Chains - Vinoth Kumar C; Poongundran Selvaprabhu (IEEE Access, 2023)
Establishing a well-functioning Supply Chain Management (SCM) system is paramount during challenging times such as pandemics, natural disasters, and international conflicts. The complexity of global supply chains necessitates efficient systems, procedures, and personnel to ensure optimal results. Poor coordination among entities can lead to increased counterfeit products, increased ocean transportation costs, more expensive freight brokerage, bottlenecks in cargo flow, congestion, and complications in product accountability. To ensure a smooth and hassle-free operation, it’s essential to maintain unambiguity and accuracy throughout every process. Therefore, it is vital to have effective systems, procedures, and personnel in place for SCM. The challenges encountered in SCM can be effectively tackled by utilizing blockchain technology. The architecture of blockchain technology is characterized by its distributed, decentralized and robust safety measures, which guarantee the integrity of data storage and its distribution across a meticulously organized ledger. Users can confidently rely on this innovative design’s transparency, reliability, and safety. Implementing blockchain technology carries immense potential in bolstering safety and privacy measures in diverse sectors, including agriculture, healthcare, Goods and Services Tax (GST), academics, e-voting and automobile. This investigation delves into the practical applications of blockchain technology for SCM. It thoroughly analyses existing research and literature to uncover the latest advancements and potential future breakthroughs in this area.